STUDY OF TECHNIQUES FOR PROCESSING CATTLE ABON IN THE M&W MEKARRAHARJA ABON PROCESSING COMPANY KEC. TALAGA DISTRICT MAJALENGKA - Sutarjo, Lele Sangkuriang; Fauzi, Rinda; Novianti, Teni; Fatimatuzahroh, Feti; Astuti, Lusia Cipto; Fajar, Rizky Brehnaputri (Jurnal Tropika Bahari, 2023)
Catfish is a fish that has important economic value, giving rise to considerable business opportunities. The demand for catfish for domestic consumption continues to increase in line with the increasing popularity of catfish as a very delicious dish. Shredded fish has a dry texture and almost no remaining water content, shredded fish usually lasts for weeks to months in airtight packaging. Apart from being made from basic meat ingredients (beef, goat, horse, pork and lamb), there are several shredded meats which are made using basic ingredients from seafood, such as tuna, catfish, tuna, eel, crab and shrimp. The aim of this research is to find out the technical aspects of processing catfish shreds and to find out the financial analysis of the catfish shredded processing business at CV.Abon M&W. The method used in this research is a descriptive method, namely using primary data where data is obtained directly from the object under study. The processing or manufacturing process goes through 3 stages including: material preparation stage, processing and finally packaging. The total production costs incurred in the catfish floss business for one month of production are Rp. 1,522,414.00. One cycle of catfish floss production produces 28 packs and in 1 month it can produce 336 packs. With a unit price of IDR 17,000.00, the monthly income obtained is IDR 5,712,000.00 and the profit in the catfish floss business in 1 month is IDR. 4,189,586.00.